The interactions between product valorisation and genetic management: Applying a common framework to analyze four cases of sheep and goat local breeds in the Mediterranean area - Lauvie A.; Hadjipavlou G.; Araba A.; Casabianca F.; Ligda C. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
In the Domestic project, funded within the ARIMNet framework, we have conducted an analysis of four case studies of valorisation of products from local sheep and/or goat breeds in Cyprus, France (Corsican region), Greece (Ipeiros region) and Morocco. For each case, data were collected from experts concerning the collective organization of both local breed management and product valorisation. These data were analysed using the same framework, which was built aiming to take into account the animal population dynamics, the breed’ products, and the stakeholder dynamics. The crossed analysis of the cases underlines the diversity of stakes for product valorisation that depends on the breed status and the type of product. We also investigated the importance of the degree of formalization of the link between the breed and the product (through a geographical indication for instance), and we concluded with a comparison of the organizational and social aspects of the interactions between local breed management and product valorisation in the four cases.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)